2018
DOI: 10.14203/oldi.2018.v3i3.207
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Risiko Kesehatan Pencemaran Timbal (Pb) Pada Kerang Hijau (Perna viridis) di Perairan Cilincing Pesisir DKI Jakarta

Abstract: <strong>Health Risk Assessment of Lead (Pb) Pollution in Green Mussel (Perna viridis) at Cilincing Waters, DKI Jakarta Littoral.</strong> Cilincing waters is one of the river estuaries on the coast of DKI Jakarta with increasing industrial and community activities. These activities certainly produce waste that contains heavy metal lead and into the water. Water pollution will affect the health of humans who interact directly or indirectly in these waters. Green mussel (Perna viridis) is one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
3
0
7
Order By: Relevance
“…Consuming green mussels in cilincing waters is no longer safe. 17 Makmur et al found that using a maximum portion size of the cilincing community of 650.70 g, the value of witnesstotoxin exposure is 1.88 g/kg b.b. the value is still below the exposure value agreed by the EFSA panel which is 5.3 g/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Consuming green mussels in cilincing waters is no longer safe. 17 Makmur et al found that using a maximum portion size of the cilincing community of 650.70 g, the value of witnesstotoxin exposure is 1.88 g/kg b.b. the value is still below the exposure value agreed by the EFSA panel which is 5.3 g/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Pengambilan uji air sampel Sungai Brangkal diambil pada musim penghujan dengan kondisi perairan dengan volume air yang meningkat. Menurut Simbolon (2018) konsentrasi timbal (Pb) yang rendah dalam perairan dipengaruhi oleh peningkatan volume perairan pada musim penghujan dapat menyebabkan proses pengenceran. Selain itu kadar timbal (Pb) pada suatu perairan dipengaruhi oleh intensitas aktivitas manusia, berkaitan dengan aktivitas industri yang menghasilkan limbah buangan serta aktivitas pembuangan sampah (Priatna et al, 2016).…”
Section: Pembahasanunclassified
“…Logam berat tergolong bahan pencemar kerena bersifat relatif stabil dan susah terurai (Hasni dkk., 2020). Logam berat yang masuk ke perairan bersumber dari debu vulkanik, pengikisan bebatuan serta kegiatan antropogenik, berupa pembuangan limbah, baik domestik maupun indutri (Maddusa dkk., 2017); (Simbolon, 2018). Peningkatan sumber logam berat di alam akan menambah tingkat pencemaran logam berat di kolom air dan sedimen perairan, yang selanjutnya akan terakumulasi pada komponen-komponen rantai makanan dalam ekosistem perairan tersebut, sehingga menyebabkan keracunan pada organisme penghuni (Sembe, 2015); (Simbolon & Purbonegoro, 2021).…”
Section: Hasil Dan Pembahasanunclassified